2007
DOI: 10.1002/glia.20472
|View full text |Cite
|
Sign up to set email alerts
|

Astroglia‐mediated effects of uric acid to protect spinal cord neurons from glutamate toxicity

Abstract: Uric acid (UA) has been demonstrated to reduce damage to neurons elicited by oxidative stress. However, our studies utilizing cultures derived from embryonic rat spinal cord indicate that an astroglia-mediated mechanism is involved in the effects of UA to protect neurons from glutamate toxicity. The damage elicted by glutamate to neurons in a mixed culture of spinal cord cells can be reversed by UA. Furthermore, addition of UA after the termination of glutamate exposure suggests that UA plays an active role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 40 publications
9
99
1
Order By: Relevance
“…By using complementary genetic approaches disrupting and overexpressing UOx, we have demonstrated that disruption of the UOx gene with a resultant rise in urate protects the nigrostriatal dopaminergic system, and conversely that transgenic overexpressson of UOx with a resultant fall in urate exacerbates dopaminergic neurodegeneration and resultant neurochemical and behavioral deficits in a 6-OHDA mouse model of PD. Neuroprotective effects of urate have been reported in various in vitro and in vivo experimental models of neurological disorders, including ischemic brain injury (13,14), multiple sclerosis (15), and spinal cord injury (16,17). However, evidence regarding urate in PD models is sparse and largely restricted to cellular models of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…By using complementary genetic approaches disrupting and overexpressing UOx, we have demonstrated that disruption of the UOx gene with a resultant rise in urate protects the nigrostriatal dopaminergic system, and conversely that transgenic overexpressson of UOx with a resultant fall in urate exacerbates dopaminergic neurodegeneration and resultant neurochemical and behavioral deficits in a 6-OHDA mouse model of PD. Neuroprotective effects of urate have been reported in various in vitro and in vivo experimental models of neurological disorders, including ischemic brain injury (13,14), multiple sclerosis (15), and spinal cord injury (16,17). However, evidence regarding urate in PD models is sparse and largely restricted to cellular models of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Urate protected cultured spinal cord neurons from glutamate toxicity [37] and was neuroprotective in models of spinal cord injury, multiple sclerosis, brain injury, and stroke [38][39][40][41]56]. This growing literature suggests a potential neuroprotective role for urate beyond PD.…”
Section: Urate Is Neuroprotective In Several Preclinical Models Of Nementioning
confidence: 99%
“…At physiologically relevant concentrations, urate was also shown to enhance function and survival of dopaminergic neurons in primary cultures of rat ventral mesencephalon [53]. Interestingly, urate-mediated effects may require its accumulation in astrocytes, suggesting a noncell-autonomous mechanism for urate's neuroprotective activity [36,37]. The mechanisms underlying urate's neuroprotective effects are not completely clear, though recent in vitro studies have begun to shed light on urate's targets.…”
Section: Urate Is Neuroprotective In Several Preclinical Models Of Nementioning
confidence: 99%
“…24 The microglia were detached from the flasks by mild shaking and applied to a nylon mesh to remove astrocytes and cell clumps. Cells were plated in 60-mm 2 dishes (8 ϫ 10 5 cells per dish) or 100-mm 2 dishes (2 ϫ 10 6 cells per dish).…”
Section: Glial Cell Culturementioning
confidence: 99%